If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(4n + -5) = 9 + -5n Reorder the terms: 8 + -1(-5 + 4n) = 9 + -5n 8 + (-5 * -1 + 4n * -1) = 9 + -5n 8 + (5 + -4n) = 9 + -5n Combine like terms: 8 + 5 = 13 13 + -4n = 9 + -5n Solving 13 + -4n = 9 + -5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '5n' to each side of the equation. 13 + -4n + 5n = 9 + -5n + 5n Combine like terms: -4n + 5n = 1n 13 + 1n = 9 + -5n + 5n Combine like terms: -5n + 5n = 0 13 + 1n = 9 + 0 13 + 1n = 9 Add '-13' to each side of the equation. 13 + -13 + 1n = 9 + -13 Combine like terms: 13 + -13 = 0 0 + 1n = 9 + -13 1n = 9 + -13 Combine like terms: 9 + -13 = -4 1n = -4 Divide each side by '1'. n = -4 Simplifying n = -4
| 7x-16+10x+9=180 | | X+2.4=5.1 | | 2b+3b=21 | | (8x^4y^-3)((x^-5y^2)/2) | | -5(2x-2)=4x-3 | | 3(x+7)=9+2x | | 9+7(x-8)=7-7(x-8) | | 3x+7-x=5+x-9 | | -7m^2-10m+8=0 | | -8(z-1)=-7z-5 | | 13y-2=26-y | | 9a+5b=11960 | | 4(n-64)= | | 6/10*x/a6 | | 6/10*x/16 | | 13-2=26-y | | 10x/96 | | -35=5x-4 | | X/3-2=5x-2( | | 2/7x-3/5x=6/35 | | -8(x+4)=-9(x+6) | | x/5=9/4 | | 1/3(c-9)=-6 | | -24=4w | | 16/12=x/4 | | 184=-2x+7(-2x+8) | | 4*7y-6+3y= | | 11x/5/7-7/10 | | 3x+4(5+2x)+13=5x-x-6 | | 2[x-7]=11 | | 4(7y-6)+3y= | | 4x-(x-0.25)=936 |